CUSTOMER RELATIONSHIP MANAGEMENT - Rosmayani M.Si (VALUTA, 2016)
This paper aims to examine various concepts associated with the development of definitions anddimensions of customer relationship management, and strive to develop a comprehensive model ofcustomer relationship management, especially in the service industry perbankan.Permasalahan be raisedin writing this paper, first how the development of the concept , definitions and dimensions of customerrelationship management and secondly, how to develop a model of customer relationship managementthat can be applied to the banking services industry. The approach used in this paper is the dimensionalapproach that examines the dimensions contained in the variables of the customer relationshipmanagement and find new dimensions in the implementation of customer relationship management.Implications academic presence in this paper theoretical understandings of the causes of failure andsuccess of the company in implementing customer relationship management. While the practicalimplications of this paper is expected to be taken into consideration for businesses, especially in thebanking services industry in the application of customer relationship management. Focus conceptuallydeveloped in the writing of this paper is to examine the dimensions of customer relationship managementthat can be prepared a model that describes the customer relationship managemet in the banking servicesindustry. Original contribution of this paper can provide a new perspective on customer relationshipmanagement CRM towards a conception more proactive approach.